2020
DOI: 10.21203/rs.3.rs-56021/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient-Centered Practices for Engaging Transgender and Gender Diverse Patients in Clinical Research Studies

Abstract: Background: The purpose of this formative study was to assess barriers and facilitators to participation of transgender and gender diverse (TGD) patients in clinical research to solicit specific feedback on perceived acceptability and feasibility of research methods to inform creation of a multisite longitudinal cohort of primary care patients engaged in care at two community health centers.Method: Between September-November 2018, four focus groups (FGs) were convened at two community health centers in Boston,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is important that staff avoid stigmatizing language [6] and use gender‐affirming language and materials during interactions with participants. While a research staff that reflects the study participants may increase participant comfort and trust and has been identified as important by TGD individuals [7], having a TGD research staff does not replace the need to incorporate a trauma‐informed perspective by everyone who interacts with study participants. Given that TGD individuals working on the study may themselves have histories of trauma, the research environment needs to support and empower all staff to address trauma and cope with secondary traumatic stress.…”
Section: Figurementioning
confidence: 99%
“…It is important that staff avoid stigmatizing language [6] and use gender‐affirming language and materials during interactions with participants. While a research staff that reflects the study participants may increase participant comfort and trust and has been identified as important by TGD individuals [7], having a TGD research staff does not replace the need to incorporate a trauma‐informed perspective by everyone who interacts with study participants. Given that TGD individuals working on the study may themselves have histories of trauma, the research environment needs to support and empower all staff to address trauma and cope with secondary traumatic stress.…”
Section: Figurementioning
confidence: 99%
“…Additionally, TGD community members have advocated for their inclusion within study teams. 30,34,[65][66][67] Using Global Community Advisory and Accountability Group feedback, PURPOSE-2 included study investigators and staff who were members of the study's priority population. 52 Diverse study teams can support participant retention efforts while minimizing REVIEW potential harm to the communities participating in the research.…”
Section: Opportunities For Participant Retention and Engagementmentioning
confidence: 99%
“…While PURPOSE‐2 participant data are forthcoming, HPTN 083 exceeded its recruitment goal and illustrated the positive impact of enhanced recruitment efforts for transgender women. Additionally, TGD community members have advocated for their inclusion within study teams 30,34,65–67 . Using Global Community Advisory and Accountability Group feedback, PURPOSE‐2 included study investigators and staff who were members of the study's priority population 52 .…”
Section: Current Gaps and Opportunities For Increasing Involvement Of...mentioning
confidence: 99%
“…17 Qualitative research suggests that transgender people are motivated to participate in trials that (1) are led or staffed by transgender researchers, (2) benefit transgender communities, (3) provide resources that address financial barriers, and (4) are integrated into health care and/or are recommended by trusted clinicians. 18,19 In addition, trials that are designed to minimize the conduct of invasive procedures that can be triggering for patients with higher exposure to physical violence may also further increase interest in clinical trial participation. 19,20 Institution-level barriers may also hinder access to clinical care and clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, well-defined institutional practices are needed to engage transgender communities to develop recruitment and retention strategies across the clinical research continuum and develop metrics for advancing inclusive research. [18][19][20] Institutions that employ transgender investigators and/or clinical research staff and utilize community-based participatory research are highly effective at recruiting transgender people, including transgender people of color to participate in clinical trials. Strategies such as these may be useful when incorporated into cancer clinical trials.…”
Section: Introductionmentioning
confidence: 99%